Determinants of Antihypertensive Medication Adherence among Hypertensive Patients in The UPT Puskesmas Datah Kotou Working Area, Murung Raya District, Central Kalimantan - Yohana Kifli; Vip Paramarta; Rahadian Malik (Jurnal Mirai Management, 2025)
Adherence to antihypertensive medication is a crucial component in hypertension management, reducing the risk of severe complications. This study aims to analyze the influence of knowledge, family support, and motivation on medication adherence among hypertensive patients in the working area of UPT Puskesmas Datah Kotou. A quantitative approach was applied using a survey of 90 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The findings revealed that knowledge, family support, and motivation significantly influenced medication adherence, contributing 26.4% to the variance. Partially, motivation had the highest impact (13.8%), followed by knowledge (9.8%) and family support (2.8%). Further analysis highlighted that low patient motivation is a critical factor in non-adherence. The study concludes that enhancing patient motivation and education, along with active family involvement, can improve adherence to antihypertensive therapy. Keywords: Hypertension, Medication Adherence, Motivation, Family Support, Knowledge